Treatment Persistence and Switching in Triptan Users: A Systematic Literature Review. Issue 7 (10th June 2014) - Messali, Andrew J.; Yang, Mo; Gillard, Patrick; Tsai, Kimberly; Tepper, Stewart J.; Bloudek, Lisa M.; Kori, Shashidhar H.
<x xml:space="preserve">Abstract</x> Objective To conduct a systematic review to evaluate persistence to and switching of triptan therapy for the acute treatment of migraine. Background Migraine affects over 12% of adults in Western countries and an estimated 36 million people in the United States. Triptans are an abortive treatment option in patients with moderate to severe migraine. Despite the safety and efficacy of triptans reported in clinical trials, observational studies have consistently demonstrated low persistence to therapy and frequent switching among products over time. Methods The following databases were researched: Medline, CENTRAL, and EMBASE. Detailed inclusion and exclusion criteria were specified a priori before conducting abstract and full‐text screening. Included studies were required to: (1) report triptan use for migraine treatment; (2) report measures of persistence and/or switching patterns; (3) study migraineurs aged 18 years or older; and (4) conduct an observational study. Studies were excluded if they (1) incorporated interventional study design; (2) lack information or relevance to outcome of interest; (3) were not original research; (4) did not clearly state the results; and (5) were not written in English. Abstracts and full‐text articles were reviewed independently by two investigators. Results Out of 595 studies identified, 380 studies were included for abstract screening. A total of 12 articles met the eligibility criteria after full‐text screening of 44 studies, including four studies from reference search. The proportion of patients that remained persistent up to six refills of an index triptan ranged from 3.2% to 12.6% and the proportion of patients that never refilled their index triptan ranged from 38% to 65.8%. In addition to those patients who discontinued, several studies reported that 5‐9% of newly initiating triptan users switch to a different triptan before refilling their original medication. Finally, several studies reported the 1‐year probability of discontinuation among a general group of triptan users (not limited to treatment naïve patients) to be between 30% and 60%. Conclusions Triptans can be a valuable option for acute treatment of migraine. However, studies have shown that treatment persistence is low. This, along with frequent switching behaviors, suggests that a significant unmet clinical need remains despite the wide availability of triptans.